CPLP: the first twenty-five years - Marques, Joseph (Conjuntura Austral, 2022)
The decision by Conjuntura Austral to dedicate a special issue to the 25th anniversary of the establishment of the Community of Portuguese Language Countries (CPLP) is to be commended. The uniqueness of the organization justifies a timely review of a small sample of its activities to date. Created in 1996, the CPLP adopted three main vectors of activity:1) the promotion and dissemination of the Portuguese language; 2) cooperation in a wide array of domains (i.e., education, health, science and technology, defense, agriculture, public administration, communication, justice, public safety, culture, sport and social communication, sustainable development, etc.); and 3) political and diplomatic coordination, especially in multilateral forums. The organization also agreed to adhere to several fundamental political principles such as the respect of the sovereignty of each member country; non-interference in domestic issues; reciprocal treatment; peace, democracy, rule of law, human rights, and social justice; territorial integrity of each member state; and the commitment to the promotion of development and cooperation.